2020
DOI: 10.1108/ijshe-07-2019-0229
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability funding in higher education: a literature-based review

Abstract: Purpose The purpose of this paper is to report a literature review on sustainability funding in higher education and an analysis of the theoretical influence on academic research. The theoretical contribution and the most influential authors were examined to better understand the intellectual structure that links the theories and authors that have researched this topic. This study not only allows comprehension of the current research scenario but also, based on the gaps identified, provides guidelines for futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 83 publications
0
16
0
1
Order By: Relevance
“…This research uses the multidimensional scaling method (MDS) and exploratory factor analysis (EFA), as suggested by Montenegro de Lima et al (2020). Among the different bibliometric research methods, for the purpose of this study, the coupling of subjects to identify trends in publications and the growth of knowledge on the topic of CF in universities stands out well.…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…This research uses the multidimensional scaling method (MDS) and exploratory factor analysis (EFA), as suggested by Montenegro de Lima et al (2020). Among the different bibliometric research methods, for the purpose of this study, the coupling of subjects to identify trends in publications and the growth of knowledge on the topic of CF in universities stands out well.…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…Other previous studies (Baldridge, 1983;Cohen and March, 1974;Weick, 1976;Millet, 1962) already identified the university as an atypical and paradoxically complex organization: ambiguous objectives, centered on the work of professionals, based on problematic technology, operates products difficult to measure, it lives with decision-making processes and forms of management that mix bureaucratic, political, collegiate and anarchic aspects, in addition to the vulnerability of the environment.…”
Section: Higher Education Institutions and Their Relations With The Balanced Scorecardmentioning
confidence: 99%
“…"pure". This presupposes the formation of a single global "educational space", with uniform standards for training specialists, in which universities will try to acquire and maintain their "competitive advantages": education is also a product that needs to be sold to the consumer, and the market price of which depends on the market demand for trained specialists (of particular importance are the issues related to the financing of science and education and the "justification of costs" [26]: technicalization as a specialization and "practical orientation" does not leave room for what was previously called "education of humanity"; moreover, we have a completely different "coordinate system" (or "conceptual framework"): "humanity" as the goal of romantic (and classical) education is the duty, not profit or "competitive advantage" -and it is outside the market. In the same vein is the idea of "continuing education": to the extent that capital is concerned, it must grow, "become obsolete" from time to time, and continually change structurally in line with market conditions.…”
Section: Research Resultsmentioning
confidence: 99%